2022
DOI: 10.1039/d1re00528f
|View full text |Cite
|
Sign up to set email alerts
|

A spherical multishell hollow carbon-based catalyst with a controllable N-species content for the oxygen reduction reaction in air-breathing cathode microbial fuel cells

Abstract: Spherical micro- and mesoporous carbon-based catalysts are often surprisingly effective at oxygen reduction reaction (ORR). Herein, a self-templated strategy was proposed to fabricate a spherical MOF (S-Terephthalic acid-MOF, S-Co-Ni-PTA-MOF) via...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…There are various strategies to introduce N to carbonbased materials, but most of them required complex, time-consuming process and expensive nitrogen sources. Wang et al [26] prepared N doped SÀ CoÀ Ni/NÀ CÀ T by melamine carbonization. As a cathode catalyst, it has good electrical performance and the high output voltage (0.63 � 0.3 V).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are various strategies to introduce N to carbonbased materials, but most of them required complex, time-consuming process and expensive nitrogen sources. Wang et al [26] prepared N doped SÀ CoÀ Ni/NÀ CÀ T by melamine carbonization. As a cathode catalyst, it has good electrical performance and the high output voltage (0.63 � 0.3 V).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al. [26] prepared N doped S−Co−Ni/N−C−T by melamine carbonization. As a cathode catalyst, it has good electrical performance and the high output voltage (0.63±0.3 V).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to single chain surfactants, these surfactants have higher surface activity, lower Kraft characteristics, stronger emulsifying and interfacial adsorption properties, and have broader application prospects in fields such as tertiary oil recovery, sterilization, and metal corrosion prevention [2][3][4]. This has also led to further research on the influence of surfactant molecules on their performance [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to increase the quantity of catalytic centers M–N x to targetedly boost the electrocatalytic ability. Co-pyrolysis of the precursor of M–N–C with nitrogenous organic compounds (urea and melamine) or introducing nitrogenous compounds by constructing special morphology can effectively increase the amount of active center sites, in which constructing special morphology can not only increase the M–N x active site but also significantly optimize the pore structure and ameliorate the dispersion of catalytic site distribution to reduce the resistance between catalyst substrates and improve the electron transfer efficiency of catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Although the M–N–C catalysts show considerable potential in the effective improvement of the catalytic performance with cost reduction, their long-term operation stability has not been effectively improved . Abundant studies have shown that the alloyed catalysts composed of multimetal and M 1 /M 2 –N–C catalysts can obtain satisfactory ORR catalytic performance accompanied by outstanding long-term stability. This may be owing to the synergistic action of multiple metals, which increases the charge imbalance on the carbon surface and improves the conductivity of catalyst materials.…”
Section: Introductionmentioning
confidence: 99%